Relationship between extrinsic factors and non-carious cervical lesions in patients of the National Hospital "Hipólito Unánue" - PERCY ALFONSO DELGADO ROJAS (Universidade Estadual de Campinas, 2021)
Non-carious cervical lesions cause destructive dental disorders that actively contribute to the progressive loss of dental structure and the immediate need for dental treatment, due to their multiple symptoms and factors that produce them. Aim: The purpose of the study was to determine the relationship between extrinsic factors and non-carious cervical lesions in patients of the National Hospital Hipólito Unánue. Methods: The research was of a descriptive correlative type. The sample consisted of male and female patients between 18 and 65 years old, who attended the carielogy service of this hospital. For data collection, 2 questionnaires were used to estimate the values of the extrinsic factors that allowed us to obtain the necessary information on the variables to be studied. Spearman's Rho was applied to determine the relationship between the variable's study. Results: According to Spearman's Rho of 0.622, compared to p-0.000 <0.01. Between the variables studied; extrinsic factors and noncarious cervical lesions there is a moderate and significant positive correlation. Conclusion: Through this section it was possible to demonstrate the existing relationship between extrinsic variable factors and non-carious cervical lesions, therefore it was concluded that there is a moderate and significant positive correlation in the sample comprised by the patients of the Hospital in mention.